Single-shot multi-keV X-ray absorption spectroscopy using an ultrashort laser-wakefield accelerator source - Kettle,B; Gerstmayr,E; Streeter,MJV; Albert,F; Baggott,RA; Bourgeois,N; Cole,JM; Dann,S; Falk,K; Gallardo,González I; Hussein,AE; Lemos,N; et al. (Physical Review Letters, 2019)
Single-shot absorption measurements have been performed using the multi-keV x rays generated by a laser-wakefield accelerator. A 200 TW laser was used to drive a laser-wakefield accelerator in a mode which produced broadband electron beams with a maximum energy above 1 GeV and a broad divergence of ≈15  mrad FWHM. Betatron oscillations of these electrons generated 1.2±0.2×106  photons/eV in the 5 keV region, with a signal-to-noise ratio of approximately 3001. This was sufficient to allow high-resolution x-ray absorption near-edge structure measurements at the K edge of a titanium sample in a single shot. We demonstrate that this source is capable of single-shot, simultaneous measurements of both the electron and ion distributions in matter heated to eV temperatures by comparison with density functional theory simulations. The unique combination of a high-flux, large bandwidth, few femtosecond duration x-ray pulse synchronized to a high-power laser will enable key advances in the study of ultrafast energetic processes such as electron-ion equilibration.